The Influence of Organizational Culture, Motivation, and Job Satisfaction on ASN Performance (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This study explores the impact of organizational culture, motivation, and job satisfaction on the performance of Civil Servants (ASN) at the Karawang Regency Environmental Service. The study involved 95 ASN participants, with data collected through a quantitative census method. Multiple linear regression analysis was conducted using SPSS 25 to evaluate the data obtained from questionnaires. The results indicate that organizational culture and motivation have a significant positive impact on civil servant performance, suggesting that as organizational culture and work motivation improve, so does the performance of civil servants. However, job satisfaction was found to have no significant effect on performance. This implies that while job satisfaction may play a role, it is less influential on civil servant performance compared to work culture and intrinsic motivation. The study also reveals that 62.3% of civil servant performance is influenced by organizational culture, motivation, and job satisfaction, while 37.7% is driven by other unassessed factors. These findings highlight the importance of fostering a positive work culture and enhancing employee motivation as key strategies for improving performance in government agencies. The study underscores the need for public sector organizations to focus on these internal factors to achieve higher performance levels.